Biosorption for removal of hexavalent chromium using microalgae Scenedesmus sp. (1st February 2019) - Pradhan, Debabrata; Sukla, Lala Behari; Mishra, Bibhuti Bhusan; Devi, Niharbala
Abstract: Biosorption was carried out in this study using the biomass of microalgae Scenedesmus sp. as adsorbent for the removal of hexavalent chromium or Cr(VI) from solution. Different relevant parameters like initial pH, contact time, initial Cr(VI) concentration, biosorbent dosage, particle size, and temperature were examined to evaluate their effect. They were found to be effective with the maximum of 92.89% Cr loading onto the biomass. The FTIR analysis revealed the presence of easily hydrolyzed functional groups like aldehydes, amides, carboxylic acids, phosphates, and halides, which charged positively below the point of zero charge at pH 2.65. The biosorption proceeded through the anionic adsorption mechanism and followed the pseudo-first order kinetic model. Its feasibility was confirmed as the experimental data closely fitted to both Langmuir and Freundlich isotherms. The biosorption was spontaneous. Its spontaneity increased with the increase of temperature. The positive entropy change suggested the randomness at the solid-liquid interface. This study recommended that the toxic Cr(VI) could be removed from different contaminated water samples in the nearby chromite mines using the microalgae biomass. However, it requires attention in some other sides like activation of biomass, interference of other ions, elevation of the experimental pH, the large biomass generation and harvesting, desorption of the Cr-loaded biomass, and recovery of the energy value of the waste biomass.